PERENCANAAN KONSTRUKSI DAN ELEMEN MESIN TURBIN ANGIN SUMBU VERTIKAL TYPE DARRIEUS - Diaurahman Diaurahman; Rudi Siswanto (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2016)
Wind energi is one of the alternative energi that can be utilized for various purposes to replace the source of fossil fuel energi. The Darrieus wind turbine includes a vertikal axis wind turbine driven by lifting force from the blade. Planning of the axis vertikal type Darrieus wind turbine is aimed to calculate the elements of Darrieus machine and make design of vertikal axis component of Darrieus vertikal turbine using Marzuki (2016) research data about NACA 2415 blend analysis with variation of blade and angle of attack. The planning method used is based on the calculation of construction and vertikal axis of vertikal axis type of wind machine by using field result data in the form of wind speed, altitude and environmental condition which produce calculation result and working drawing of each machine element. The results of planning engine eleman on vertikal axis wind turbine Darrieus with 3 pieces airfoil shaped type NACA 2415 chord 30 cm has a diameter and height of 1 meter. Using ST-42 shaft 17-25 mm in diameter with length 1640 mm retained 2 bearing pieces with numbers 30203 and 6204. Transmission using belt and pulley type with 1: 14 increase ratio. Frame using Lx steel profile size 30x30 with total length ± 15 m. The use of materials such as composites is preferable to reduce turbine load without affecting the strength and durability of the turbine.